Big plans : the allure and folly of urban design - Kolson, Kenneth L., 1945- (Center books on contemporary landscape design., 2001)
This work springs from the idea that human aspirations for the city tend to overstate the role of rationality in public life. The author explores the part serendipity plays in urban experience.